Sexology as a profession in Portugal: sociographical composition and self-nomination of Portuguese sexologists - Alarcão, V. (2017)
Objectives: The objective of this study was to describe the socio-demographic characteristics, the initial profession and training in sexology, sex therapy and psychotherapeutic techniques of Portuguese sexologists. Methods: As part of an European survey on sexology as a profession (Euro-Sexo), a questionnaire was mailed to all Portuguese sexologists. Results: Portuguese sexologist is in average 43 years old, is mainly female, a non-physician, and has training in sexology. Age, gender, profession, clinical practice and educational background in sexology, research practice in sexology and sexual education made a significant contribution to the prediction of self-nomination as a sexologist. Conclusions: An interesting diversity of sexology professions, from medical to non-medical fields was identified, and its influence on the practice of sexual medicine was discussed.